Belief system of future teachers on Education for Sustainable Development in math classes - Vásquez, Claudia (2020)
This paper studied the belief system of future Chilean teachers of Early Childhood Education and Primary Education regarding their competencies to incorporate Education for Sustainable Development (EDS) in the classroom, specifically, in math classes. To this end, a survey was applied to 87 Primary Education preservice teachers and 58 Early Childhood Education preservice teachers, which was analyzed from an interpretative approach. Results are not clear regarding ESD and its scope, despite being valued. In addition, there is a clear need for training in this regard and the potential of mathematical education as a tool to incorporate ESD into the school classroom. It is concluded that ESD-related competencies need to be incorporated in initial and permanent teacher training programs in a transversal way, in our case for Mathematics Education.